THE PROPOSED DESIGN OF ASSEMBLY LINE TAIL UNIT CN235 AT PT DIRGANTARA INDONESIA - MELINDA SITORUS, GRACE
CN235 is one of PT Dirgantara Indonesia's high demand aircraft products. PT DI estimates that CN235’s demand will increase to 6 units a year. However, the current production capacity of CN235, specifically the major subassembly tail unit, is only 3 units a year. CN235 production speed highly depends on the assembly process which takes 63% of the total production time. Research focused on improving assembly line’s process to increase the production capacity of PT and meet the demand. There are two components of CN235’s tail unit that have not reached the production target yet, RH Horizontal Structure and Rudder Structure. Moreover, the workload between stations on both components is still not balanced. This research aims to design an assembly line that meets the takt time and has a better smoothness index value than the actual system for the RH Horizontal Structure and Rudder Structure. The research step taken is to reassign tasks to stations by using an integer nonlinear programming. The model’s objective function is to minimize the sum of squared deviation between takt time and station time. The constraints used in this model are negative zoning constraint, precedence constraint, and cycle time constraint. The computational result of the development model reduced the smoothness index of the RH Horizontal Structure for 34% while the Rudder Structure for 61%. Cycle time of tail unit CN235 reduced from 587 hours to 294 hours. The total cost needed to implement the solution is Rp895.680.000. The solution effectively increases the production capacity of tail unit CN235 to 6 units a year.